Comparison between Lidocaine Spray and Oral Paracetamol for Pain Reduction during Amniocentesis in Second Trimester Pregnancy; A Randomize Controlled Trial - Sriwattanapong, Chanokrak; Pongrojpaw, Densak; Chanthasenanont, Athita; Pattaraarchachai, Junya; Suwannarurk, Komsun (Siriraj Medical Journal, 2024)
Objective: The aim of this study was to compare the efficacy of lidocaine spray and oral paracetamol on pain reduction in pregnant women in the second trimester during amniocentesis. Materials and Methods: This was a prospective randomized-controlled trial study conducted at Maternal and Fetal Medicine unit, Thammasat University Hospital, Pathum Thani, Thailand between June 2022 and April 2023. Participants were pregnant women who underwent amniocentesis during gestational age between 15 and 20 weeks. They were allocated into three groups namely lidocaine, paracetamol and control groups. Subjects in lidocaine group received 8 puffs of 10% lidocaine (80 mg) spray onto the marked puncture site for five minutes before amniocentesis and ingested 1 placebo tablet 1 hour before procedure. Paracetamol group ingested 650 mg paracetamol orally 1 hour before amniocentesis and received 8 puffs of normal saline spray on the marked puncture site. Control group received 8 puffs of normal saline spray onto the marked puncture site for five minutes before amniocentesis and ingested 1 placebo tablet 1 hour before amniocentesis. Expected pain (Te), during procedure (T0), 15 and 30 minutes after procedure (T15 and T30) were evaluated based on 10-cm visual analog scale (VAS). Results: A total of 510 pregnant women were recruited and divided equally (170 cases per group). Mean maternal age was 36.1 years old. Demographic characters of three groups were comparable. Lidocaine had more pain reduction than paracetamol and control group at T0, T15 and T30 (at T0: 3.06±2.16 vs 3.96±2.42 vs 3.92±2.35, P value < 0.001, T15: 1.12±1.38 vs 1.92±1.47 vs 1.98±1.87, P value < 0.001, T30: 0.64±0.95 vs 1.33±0.97 vs 1.09±1.44, P value < 0.001). However, paracetamol had no significant difference in pain reduction compared to control group. Conclusion: Lidocaine spray before amniocentesis had more efficacy on pain reduction during amniocentesis, 15 and 30 minutes after procedure.